Stochasticity in mammalian cell growth rates drives cell-to-cell variability independently of cell size and divisions - Ethan Levien; Joon Ho Kang; Kuheli Biswas; Scott R. Manalis; Ariel Amir; Teemu P. Miettinen (Proceedings of the National Academy of Sciences, 2026)
Cell growth rates exhibit cell-intrinsic cell-to-cell variability, which influences cell fitness and size homeostasis from bacteria to cancer. It remains unclear whether this variability arises from stochasticity in cell growth or division processes, or from cell-size-dependent growth regulation. To separate these potential sources of growth variability, single-cell growth rates need to be examined across different timescales. Here, we study cell size and growth regulation by tracking lymphocytic leukemia cell mass accumulation with high precision and minute-scale temporal resolution along long ancestral lineages. We first show that correlations between growth rates and cell-size nor asymmetric divisions explain cell-to-cell growth variability. We then isolate growth fluctuations by smoothing and detrending the growth rate dynamics using a Gaussian process regression. We find that these growth fluctuations drive cell-to-cell growth variability within ancestral lineages despite being independent of cell divisions, cell cycle, and cell size. Overall, our results provide a quantitative framework for understanding single-cell growth rates, and indicate that cell-intrinsic long-term patterns in growth are a byproduct of short-term growth fluctuations.